ANALISIS PENDAPATAN RUMAH TANGGA PETANI PADI DI SULAWESI SELATAN - Misbahuddin Misbahuddin (Jurnal Bisnis dan Kewirausahaan, 2016)
The aim of this research is to calculate and analyze standard about wide optimum farmlands (Land Operation) of the poor farmers households, the income of rice farm, and decent living needs of the poor farmers households in South Sulawesi, the approach methods used are mixed methode approach between quantitative method and quantitative methode. The tools analysis used are as follows : the analysis of income and cost or farm : the analysis of revenue and cost ratio (R/C ratio) the analysis of famer consumption; and Z score model used as the tools of analysis in calculating wide optimum farm lands and the income of poor farmers households in their rice farm with total number of respondents are 400 rice farmers. The results of finding for income of the poor farmers households who owners rice fields and also as cultivators of their rice fileds are average Rp. 1,199,408,33/month, for a farmer only or a cultivator only (profit sharing system) Rp. 599,704,17/month, while a farmworker only Rp. 198,148,15/month. Production capacity for technical irrigation rice fields average show 7,1 ton/ha. per crop, while for rice fields of rainfed (tadah rain) average show 5,12 ton/ha. per crop. For rice fields of rainfed the farmers’ consumption needs for decent living generally show Rp. 6,808,500 per year or equal to 801 kilogram rice. Standard for optimum farmlands are 0,95 ha/farmer, the need of rice fields for poor farmer who owns rice field namely 0,88 ha/farmer, cultivating lands owned by other persons are 1,65 ha/farmer. While, rice fields of rainfed which standard namely 0,38 ha/farmer for the need rice fields to fulfill its KHL 0,37 ha/farmer for owner of rice fields and not cultivate the rice fields, while cultivating farmer/profit sharing farmer owned by other persons the needs of rice fields are 0,71 ha/farmer. Therefore, the strategy suggested to increase the prosperity of farmers are defensive.